The Effect of a Carbon Fiber Layer Between the Cathode and the Current Collector on Battery Cell Performance - Jaswinder Sharma; Runming Tao; Georgios Polizos; Ruhul Amin; Yue Feng; Junbin Choi; M. Shahriar; Jianlin Li (Fibers, 2025)
Contact resistance between the cathode active material (CAM) and the Al current collector can be reduced by applying carbon coatings to the Al current collector surface. However, this process requires an additional step of carbon layer coating on the current collector, which increases both manufacturing costs and processing time. In the present work, an interlayer of continuous unsized carbon fibers aligned in one direction (CF interlayer), is introduced between the Al current collector and the NMC811 cathode during cathode deposition on the Al current collector. This single-step approach eliminates the need for the additional carbon layer coating on the current collector. Additionally, this approach removes the use of toxic solvents and insulative polymers used for making the carbon coating. The CF interlayer improves the rate capability at higher C-rates. The CF interlayer lowers the contact resistance between the cathode particles and the current collector while improving the activation energy of charge transfer. The peel test showed that the CF interlayer does not affect the adhesion strength of the cathode layer with the current collector.